Efektivitas Kinerja Pemerintah Desa dalam Pengelolaan PAMSIMAS - Ummi Hani, Nur; Fahmal, Muin; Qamar, Nurul; Arifin, Muhammad Ya’rif (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: This study aims to determine and understand the effectiveness of the performance of the Village Government in the Management of Community-Based Water Supply and Sanitation Programs in Tanah Bumbu Regency. This study uses empirical research methods using primary and secondary data types. The results of this study indicate that the Village Government has not been effective in managing the Community-Based Water Supply and Sanitation Program or PAMSIMAS. This is judged by the fact that there are still programs that do not function in several villages, one of which is due to facilities that can no longer be used. The general factors that usually become obstacles include lack of funds for asset maintenance, inadequate facilities and infrastructure, the arrival of the dry season causing water sources to dry up, the amount of water produced is not proportional to the amount of water needed, and the condition of the soilwich are less able to withstand water infiltration. Research recommendations from the Village Government should encourage the community to be active together in program utilization and asset maintenance by seeking funds either through community contributions or requesting assistance from the city/district government in the form of donations, or nearby companiesvillage. Country drop provide a legal umbrella made by the Regency Government so that the distribution of the budget for the program can run as it should and does not conflict with the applicable laws and regulation, a well as clarify the implementing rules for maintenamce of the program the facility. Abstrak: Penelitian ini bertujuan untuk mengetahui dan memahami efektivitas kinerja Pemerintah Desa dalam pengelolaan Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat DI Kabupaten Tanah Bumbu. Penelitian ini menggunakan metode penelitian empiris dengan menggunakan jenis data primer dan sekunder. Hasil penelitian ini menunjukkan bahwa Pemerintah Desa belum efektif dalam pengelolaan Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat atau PAMSIMAS. Hal ini dinilai dari masih adanya program yang tidak berfungsi di beberapa desa salah satunya akibat fasilitas yang tidak dapat lagi digunakan. Adapun faktor umum yang biasa menjadi hambatan antara lain, kurangnya dana untuk pemeliharaan aset, sarana dan prasarana kurang memadai, datangnya musim kemarau menyebabkan sumber air menjadi kering, jumlah air yang dihasilkan tidak sebanding dengan jumlah air yang dibutuhkan, serta keadaan tanah yang kurang mampu menahan resapan air. Rekomendasi penelitian Pemerintah Desa seharusnya mendorong masyarakat untuk bersama- sama aktif dalam pemanfaatan program dan pemeliharan aset dengan mencari dana baik melalui iuran di masyarakat atau meminta bantuan kepada pemerintah kota/kabupaten berupa sumbangan, atau perusahaan di sekitar desa. Memberikan payung hukum yang dibuat oleh Pemerintah Kabupaten agar penyaluran anggaran untuk program tersebut bisa berjalan sebagaimana mestinya dan tidak bertentangan dengan peraturan perundang-undangan yang berlaku, serta memperjelas aturan pelaksana untuk dilakukan pemeliharaan terhadapat fasilitas tersebut.